Sliding Mode Controllers for Standalone PV Systems: Modeling and Approach of Control - Y. Chaibi; M. Salhi; A. El-jouni (International Journal of Photoenergy)
This paper presents a single-phase standalone photovoltaic (PV) system with two stages of converters. The aim of this work is to track the maximum power point (MPP) so as to transfer the maximum available power to the load and to control the output current in order to feed the AC load by a sinusoidal current. These goals are attained by using the sliding mode to design control laws in order to command the boost DC-DC and the inverter switches. Thus, a maximum power point tracking (MPPT) and an output current controller based on the sliding mode are proposed. The innovative aspect of this work is to propose a standalone PV system with the controllers based only on the sliding mode control approach. The proposed system is modeled and simulated under MATLAB Simulink under fast variations of irradiance and temperature. Then, the obtained results using the suggested MPPT are compared to those using the incremental conductance (IC) method. These results demonstrate the superiority of the sliding mode MPPT in terms of the tracking speed, the efficiency, and the time of response. Moreover, the current controller provides an output current of high quality with a THD of 3.47%. Furthermore, for accurate results, these controllers are evaluated under the fluctuations of two daily climatic profiles (sunny and cloudy) and compared those of the IC method. The results illustrate that the sliding mode MPPT has the potential of generating more electrical energy than the IC MPPT with benefits of up to 13.02% for the sunny daily profile and 27.57% for the cloudy one.